Tawhid and the relevantisation of Qur’anic exegesis to muslim political life: An exegetical interpretation of Al-Turabi’s Tafsi - Ibrahim , Esam Eltigani Mohamed; Zein, Ibrahim Mohamed (2013)
In his recently published Qur’Énic exegesis entitled al-TafsÊr al-TawÍÊdÊ, Hasan al-Turabi argued that the Qur’Énic discourse needs to be understood in accordance with the contemporary state of the Muslims. Its meanings must be interpreted in a rational manner. Most importantly, any attempt of a rationalistic interpretation must follow the methodology of TawÍÊd. This research is an exegetical interpretation of al-Turabi’s writings about the concept of TawÍÊd and his thesis of Qur’anic exegesis. The research relies on analytic and inductive methodologies to reconstruct a coherent understanding of al-Turabi’s position on Qur’Énic exegesis. The main postulate of al-Turabi’s position is the utilization of TawÍÊd in a comprehensive way. This means that all of life including politics is a complete system geared toward worshiping Allah (à). Based on this notion, al-Turabi criticized past and present Muslims, asserting that they missed the essence of TawÍÊd when they divorce politics from religion after the era of the first guided khalifas. This situation left its impact on all the sciences of Islam including Qur’Énic exegesis. As a result, nowadays reciting and memorizing the Qur’Én does not purify one’s public life. Religiosity, therefore, has become hypocrisy. For this situation to be reformed and for Islam to be correctly implemented, the Qur’Én must be interpreted in such a way that is a guide for life without differentiating the private sphere from the public one. The importance of this research, therefore, is that it presents the contribution of one of the eminent figures in the international Islamic movement on the relevantisation of the Qur’Én to contemporary human life.